Boundary blurred : a seamless customer experience in virtual and real spaces : proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference /: a seamless customer experience in virtual and real spaces : proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference. ([2018]) - Unknown
No abstract available